Effect of Water Fuel Emulsion on Performance and NOx Emissions of Diesel Engine - Beny Cahyono; Aguk Zuhdi Muhammad Fathallah; . Semin; Nauval Pahlevi (International Journal of Marine Engineering Innovation and Research, 2017)
NOx as one of the exhaust emissions is harmful to human health. Many methods can reduce NOx emissions, one of them is water in fuel emulsion. By using experiment, research has been conducted in surfactant selection. The results of experiment show 4 surfactant, which is best used to the diesel engine is tween 80 and span 80. This experiment needs some water contents variation emulsifier with 10%, 15%, and 20%. In this different variation of water is very influential on performance and NOx emissions. By using water fuel emulsion of 10% in SFOC has been increase 216,2 g/Kwh or 11.6% compared to Pertamina Dex of fuel.  However, the water used in fuel emulsion of 15% and 20% in SFOC increased to compare 10% emulsion. The effect of water use in fuel emulsion has been reduce NOx emission. Water in fuel emulsion has been decrease 50.5%. Generally, the emission level of a  diesel engine that using water in fuel emulsion has been improved until entering on Tier 3 specification of IMO rules